Design of a Slab Tamm Plasmon Resonator Coupled to a Multistrip Array Waveguide for the Mid Infrared - Gerald Pühringer; Cristina Consani; Reyhaneh Jannesari; Clement Fleury; Florian Dubois; Jasmin Spettel; Thang Duy Dao; Gerald Stocker; Thomas Grille; Bernhard Jakoby (Sensors, 2022)
In this work, we present and analyze a design of an absorber–waveguide system combining a highly sensitive waveguide array concept with a resonant selective absorber. The waveguide part is composed of an array of coupled strip waveguides and is therefore called a coupled strip array (CSA). The CSA is then coupled to the end of a slab Tamm plasmon (STP-) resonator, which is composed of a quasicrystal-like reflector formed by the patterning of a silicon slab and an interfacing tungsten slab. The concept describes an emitter–waveguide or waveguide–detector system featuring selective plasmon-enhanced resonant absorption or emission. These are crucial properties for corresponding optical on-chip integrated devices in context with evanescent field absorption sensing in fluids or gases, for example. Thus, the concept comprises a valuable and more cost-effective alternative to quantum cascade lasers. We designed the lateral dimensions of the STP resonator via a simple quasi-crystal approach and achieved strong narrowband resonances (emittance and Q-factors up to 85% and 88, respectively) for different silicon thicknesses and substrate materials (air and silicon oxide). Moreover, we analyze and discuss the sensitivity of the complete emitter–waveguide system in dependence on the slab thickness. This reveals the crucial correlation between the expected sensitivity assigned to the absorber–waveguide system and field confinement within the silicon.